Hak dan Kewajiban Istri yang Berkarier: Studi Komparatif antara Kitab ‘Uqudullujain dan Kitab Fikih Wanita Yusuf Qardhawi - Muhammad Jufri; Rizal Jupri (Istidlal: Jurnal Ekonomi dan Hukum Islam, 2019)
The rights and obligations of husband and wife according the book of ‘Uqudullujain is not some different from the books of fiqh for women. It's just that the book of ‘Uqudullujjain the description of the obligations of the wife is more, with the reason that the wife is like a prisoner for her husband. Whereas the rights and obligations of a wife who have a career according to the book ‘Uqudullujain and the book of fiqh for women are the same as the rights and obligations of the wife normally. But according to the book of ‘Uqudullujain the rights of the wife can be hindered if the wife works without the permission of the husband. Whereas according to the book of Jurisprudence Women are not hindered because the husband's permission is not required, only the work must be in accordance with the feminine nature of women and permitted by the Shari'ah.